A low cost technique for development of ultra-high resolution topography: application to a dry maar’s bottom - Jaime Jesús Carrera-Hernández; Gilles Levresse; Pierre Lacan; José Jorge Aranda-Gómez (Revista Mexicana de Ciencias Geológicas)
We developed an ultra-high resolution Digital Surface Model (DSM) of a 1.2 km ×1.2 km dry maar bottom located in Parangueo, Mexico. This maar is unique by the fact that it displays a large number and variety of structures associated with active deformation and high albedo sediments. We used a small Unmanned Aerial Vehicle (quad- copter) and a consumer grade camera to develop both a DSM and an orthophoto at a resolution of 4.7 cm through the use of Structure from Motion (SfM) algorithms from PhotoScan Pro, a commercially available software. Using the coordinates of 31 Ground Control Points measured with an RTK GPS, the residuals of the DSM had an RMSE=3.3 cm and a mean of 2.6 cm on the horizontal, with an RMSE=1.8 cm and a mean=-0.3 cm on the vertical. With this methodology we were able to construct a three dimensional model of unprecedented detail showing all structures (fractures, domes and escarpments) that have been cre- ated due to the active deformation of the dry bed lake. We conclude that the use of both UAVs and SfM provides accurate high resolution DSMs that can be obtained at a low cost, even in areas with highly reflective surfaces. Furthermore, this methodology can be applied on different dates to create a time series of high resolution DSMs, which can be used to determine subsidence or uplift rates in areas with ac- tive deformation.